Major improvement of percutaneous cardiovascular procedure outcomes with radial artery catheterisation: results from the PREVAIL study. Issue 6 (26th November 2008) - Pristipino, C; Trani, C; Nazzaro, M S; Berni, A; Patti, G; Patrizi, R; Pironi, B; Mazzarotto, P; Gioffrè, G; Biondi-Zoccai, G G L; Richichi, G
Abstract : Objective: To obtain a "snapshot" view of access-specific percutaneous cardiovascular procedures outcomes in the real world. Design: Multicentre, prospective study performed over a 30-day period. Setting: Nine hospitals with invasive cardiology facilities, reflecting the contemporary state of healthcare. Patients: Unselected consecutive sample of patients undergoing any percutaneous cardiovascular procedure requiring an arterial access. Interventions: Percutaneous cardiovascular procedures by radial or femoral access Main outcome measures: The primary outcome was the combined incidence of in-hospital (a) major and minor haemorrhages; (b) peri-procedural stroke; and (c) entry-site vascular complications. The secondary outcome was the combined incidence of in-hospital death and myocardial infarction/reinfarction. For analysis purposes, outcomes were allocated to arterial access-determined study arms on an intention-to treat basis. Multivariable analysis adjusted using propensity score was performed to correct for selection bias related to arterial site. Results: A total of 1052 patients were enrolled: 509 underwent radial access and 543 femoral access. In both groups, 40% underwent a coronary angioplasty. Relative to femoral access, radial access was associated with a lower incidence both of primary (4.2% vs 1.96%, p = 0.03, respectively) and secondary endpoints (3.1% vs 0.6%, p = 0.005, respectively). Multivariate analysis, adjusted for procedural and clinical confounders, confirmed that intention-to-access via the radial route was significantly and independently associated with a decreased risk both of primary (OR 0.37, 95% CI 0.16 to 0.84) and secondary endpoints (OR 0.14, 95% CI 0.03 to 0.62). Conclusions: Our study indicates strikingly better outcomes of percutaneous cardiovascular procedures with radial access versus femoral access in contemporary, real-world clinical settings.